Design and preliminary evaluation of a self-steering, pneumatically driven colonoscopy robot. (3rd April 2017) - Dehghani, Hossein; Welch, C. Ross; Pourghodrat, Abolfazl; Nelson, Carl A.; Oleynikov, Dmitry; Dasgupta, Prithviraj; Terry, Benjamin S.
Abstract: Colonoscopy is a diagnostic procedure to detect pre-cancerous polyps and tumours in the colon, and is performed by inserting a long tube equipped with a camera and biopsy tools. Despite the medical benefits, patients undergoing this procedure often complain about the associated pain and discomfort. This discomfort is mostly due to the rough handling of the tube and the creation of loops during the insertion. The overall goal of this work is to minimise the invasiveness of traditional colonoscopy. In pursuit of this goal, this work presents the development of a semi-autonomous colonoscopic robot with minimally invasive locomotion. The proposed robotic approach allows physicians to concentrate mainly on the diagnosis rather than the mechanics of the procedure. In this paper, an innovative locomotion approach for robotic colonoscopy is addressed. Our locomotion approach takes advantage of longitudinal expansion of a latex tube to propel the robot's tip along the colon. This soft and compliant propulsion mechanism, in contrast to minimally invasive mechanisms used in, for example, inchworm-like robots, has shown promising potential. In the preliminary ex vivo experiments, the robot successfully advanced 1.5 metres inside an excised curvilinear porcine colon with average speed of 28 mm/s, and was capable of traversing bends up to 150 degrees. The robot creates less than 6 N of normal force at its tip when it is pressurised with 90 kPa. This maximum force generates pressure of 44.17 mmHg at the tip, which is significantly lower than safe intraluminal human colonic pressure of 80 mmHg. The robot design inherently prevents loop formation in the colon, which is recognised as the main cause of post procedural pain in patients. Overall, the robot has shown great promise in an ex vivo experimental setup. The design of an autonomous control system and in vivo experiments are left as future work.